Influence of row density and foliar humic acid application on growth parameters, yield and yield components of Niger (Guizotia abyssinica Cass.) in Erbil - Zahra Suleiman Muhammed; Bahar Jalal Mahmood (Zanco Journal of Pure and Applied Sciences, 2024)
A field experiment was undertaken during the Autumn growing season of 2020 at the experimental farm of Qalamurtga - Erbil to study the effect of three Niger cultivars (Bengalnuglue, Karal and Animax, two plant geometry (45 and 60 )cm between rows and three levels of humic acid (0, 350 and 700 mg L-1) on Niger (Guizotia abyssinica Cass.) growth, yield and its component using factorial RCBD experimental design with three replicates. The results indicated that Animax cultivar, 60 cm plant spacing and 700 mg L-1 humic acid foliar application obtained the highest value of chlorophyll content (SPAD) and number of capita plant plant-1 with values of (40.31, 39.98 and 40. 52) and (30.49, 27.88, 27.91) respectively, while seed yield values (278.34, 301.30 and 282.73) kg ha-1 for Animax cultivar, 45cm distance between rows and spraying of 700 mg L-1 humic acid respectively. The combination between Animax cultivar – 45cm between rows -700mg L-1 humic acid (C3 × G1 × HA2) recorded the highest value for seed yield which was 360.41 kg ha-1. The interaction treatment (C3xG2xHA2) recorded the highest value of primary and secondary branches, leaf area and leaf area index, number of capita plant-1 and weight of 1000 seeds (g) with the values (19.66 branch plant-1, 30.00 branch plant-1, 49.01 cm2, 0.37, 37.70 capita plant-1 and 2.70g) respectively.